2021
DOI: 10.1080/15440478.2021.1966565
|View full text |Cite
|
Sign up to set email alerts
|

Physico-mechanical Properties of Naturally Dyed Jute-banana Hybrid Fabrics

Abstract: Ligno-cellulosic natural fiber like Banana can be acclimated to manufacture hybrid or union fabric with mostly used jute fiber which can get colossal popularity as a wearable product because of the health and hygiene issues. Banana fibers, extracted from the sheath, can be utilized for manufacturing fiber, can diminish the pressure on the jute fiber. It will be very frugal, and ineluctably it will be a great opportunity to blend it with the other natural fiber. In this study, a Jute-Banana hybrid fabric (JBHF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They found that the bleached banana fiber blended yarn was much more productive than the grey banana fiber blended yarn. Hassan et al developed a naturally dyeable banana fiber-jute fiber blend and tested various aspects of its physical and mechanical properties, such as strength and tensile rate, which showed that it is resistant to color loss (Figure 1), good quality, and abrasion resistance [10]. At the same time, it also reduces the burden on the amount of jute used in making garments.…”
Section: Fiber Blend Of Banana Fibermentioning
confidence: 99%
“…They found that the bleached banana fiber blended yarn was much more productive than the grey banana fiber blended yarn. Hassan et al developed a naturally dyeable banana fiber-jute fiber blend and tested various aspects of its physical and mechanical properties, such as strength and tensile rate, which showed that it is resistant to color loss (Figure 1), good quality, and abrasion resistance [10]. At the same time, it also reduces the burden on the amount of jute used in making garments.…”
Section: Fiber Blend Of Banana Fibermentioning
confidence: 99%
“…This study is also a key factor in using natural waste materials and developing useful products. In case of Banana fiber, it is mainly collected from the pseudo stem of the Banana plant [ 7 ]. A process called Tuxing is used to collect the banana fiber from the Banana pseudo stem.…”
Section: Introductionmentioning
confidence: 99%
“…Jute soft, golden, and silky-shiny vegetable fiber, is commonly known as the "Golden Fiber" and is cultivated primarily in Bangladesh and India. The South Asian region, particularly Bangladesh and India, is the primary producer of jute, accounting for approximately 95% of global jute production [1][2][3]. Nepal and Myanmar also produce small quantities of jute.…”
Section: Introductionmentioning
confidence: 99%